2019
DOI: 10.3390/nu11122907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera on Glycaemia and Insulin Levels: A Review of Animal and Human Studies

Abstract: Diabetes and related neurological complications are serious worldwide public health problems. The increasing number of affected individuals make it necessary to implement novel nutritional and therapeutic interventions. The tree Moringa oleifera (MO) has been used as a food source and for traditional medicine purposes due to possible antihyperglycemic, antioxidant, anti-inflammatory, and lipid regulating properties. These properties may be explained by the presence of numerous phytochemicals in the leaves, fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 78 publications
1
33
0
2
Order By: Relevance
“…Similar results were reported in lactating goats that fed fresh MF [17]. On the other hand, several reports confirmed the hypoglycemic effect of M. oleifera [29][30][31]. Our findings partially agreed with Meel et al, [32] who reported that replacing the concentrate feed with the of leaves M. oleifera in Sirohi goat kids increased hemoglobin, RBC, PCV, serum total protein, globulin, and albumin level while serum glucose level decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported in lactating goats that fed fresh MF [17]. On the other hand, several reports confirmed the hypoglycemic effect of M. oleifera [29][30][31]. Our findings partially agreed with Meel et al, [32] who reported that replacing the concentrate feed with the of leaves M. oleifera in Sirohi goat kids increased hemoglobin, RBC, PCV, serum total protein, globulin, and albumin level while serum glucose level decreased.…”
Section: Discussionsupporting
confidence: 92%
“…An increased in WBC counts can occur aberrantly as a result of an infection, cancer, or prescence of xenobiotics [10]. The decrease in RBC, Hb and increase in WBC by DCF-Potassium was previously reported [11]. The decrease in blood parameters caused by this drug may be attributed to its harmful effects on bone marrow and haematopoietic organs [12,13].…”
Section: Discussionmentioning
confidence: 88%
“…Optimized nutrition through supplementing one´s diet with plant derived phytochemicals has attracted significant attention in preventing the onset of many chronic diseases and metabolic abnormalities, such as dyslipidemia, insulin resistance, hypertension, glucose intolerance, systemic inflammation, and oxidative stress [ 64 ]. Experimental studies demonstrate that Moringa oleifera leaf extracts, which are rich in polyphenols, delay the onset of diabetes [ 30 , 65 ]. Although various in vitro/in vivo studies demonstrate the beneficial effects of M. oleifera phytochemicals in reducing the risk of chronic diseases, significantly more metabolic evidence is required to define a particular target(s) where the phytochemicals act as a modulator (inhibitor or activator) of diverse cellular pathways or specific enzymes.…”
Section: Resultsmentioning
confidence: 99%